Roles of repressive epigenetic machinery in lineage decision of T cells. Issue 2 (23rd April 2013) - Naito, Taku; Taniuchi, Ichiro
Summary DNA methylation and histone modifications are central to epigenetic gene regulation, which has been shown to play a crucial role in development. Epigenetics has often been discussed in the context of the maintenance of cell identity because of the heritable nature of gene expression status. Indeed, crucial roles of the epigenetic machinery in establishment and maintenance of particular lineages during early development have been well documented. However, unexpected observation of a developmental plasticity retained in mature T lymphocytes, in particular in CD4+ T‐cell subsets, by recent studies is accelerating studies that focus on roles of each epigenetic pathway in cell fate decisions of T lymphocytes. Here, we focus on the repressive epigenetic machinery, i.e. DNA methylation, histone deacetylation, H3K9 methylation and Polycomb repressive complexes, and briefly review the studies examining the role of these mechanisms during T‐lymphocyte differentiation. We also discuss the current challenges faced when analysing the function of the epigenetic machinery and potential directions to overcome the problems.